The Real-Life Effectiveness and Care Patterns of Type 2 Diabetes Management in Greece - Pagkalos, Emmanuel; Thanopoulou, Anastasia; Sampanis, Christos; Bousboulas, Stavros; Melidonis, Andreas; Tentolouris, Nicholas; Alexandrides, Theodoros; Migdalis, Ilias; Karamousouli, Eugenia; Papanas, Nikolaos (Experimental and Clinical Endocrinology & Diabetes, 2018)
Aim To investigate the prevalence of hypoglycaemia during sulfonylurea (SU) treatment of type 2 diabetes mellitus (T2DM) in Greece and its influence on glycaemic control, treatment adherence and quality of life (QoL).Patients and methods This was a retrospective cross-sectional study. We included 383 T2DM patients ≥30 years old on treatment with SU in monotherapy or in combination with metformin for at least 6 months. Patients were requested to fill in retrospective questionnaires on hypoglycaemia experience, adherence, weight gain and lifestyle/behavioural factors along with QoL (EQ-5D-3L), treatment satisfaction (TSQM), and fear of hypoglycaemia (HFS-II Worry scale).Results HbA1c<7% was found in 161 (42.0%) patients. In total, 165 (43.1%) patients reported hypoglycaemic symptoms during the previous 6 months: 41.6% (67/161) of those with HbA1c <7% and 44.1% (98/222) of those with HbA1c ≥7%. Glycaemic control was achieved by 43.1% (94/218) of patients without hypoglycaemia and 50.0% (41/82), 36.8% (25/68) and 6.7% (1/15) of patients with mild, moderate or severe hypoglycaemia, respectively (p=0.013). In multivariate analysis, both occurrence (none vs. mild/moderate/severe) and severity (none vs. mild vs. moderate vs. severe) of hypoglycaemia were significantly associated with impaired global treatment satisfaction (p=0.002 and p<0.0001 respectively) and HFS-II Worry scale scores (both p<0.0001), while lower QoL (EQ-5D (UK) Index) was related to hypoglycaemia severity (p=0.024) only. Finally, treatment adherence was associated with increased (none/mild vs. moderate/severe) hypoglycaemia severity in univariate analysis (p=0.019).Conclusion A high prevalence of patient treated with SU reported hypoglycaemia in Greek healthcare settings with negative effects on treatment satisfaction, patient worry and adherence. Severity of hypoglycaemic symptoms was associated with reduced glycaemic control.
Keywords: type 2 diabetes; sulfonylurea; hypoglycaemia; therapy outcome